THE ROLE OF RELIGIOSITY ON HALAL PRODUCT PURCHASING DECISION CASE STUDY : WARDAH COSMETICS - Amalia, Farah (Journal of Digital Marketing and Halal Industry, 2019)
The purpose of this study is to examine the effect of religiosity in making decisions about purchasing halal cosmetic products. This study uses regression analysis using purposive sampling technique that is sampling in the form of characteristics that have been determined by researchers. The results showed that religiosity affects Muslim consumers in the decision making to purchase halal cosmetic products. Practical implications for the cosmetics industry is to focus on product development based on the concept of halal in order to participate in the global market competition. The importance of considering consumer religiosity in order to gain recognition from national and international markets so that the image of the cosmetics industry has a place in the hearts of consumers.